Direct catheter-based thrombectomy in acute ischaemic stroke performed collaboratively by cardiologists, neurologists and radiologists: the single-centre pilot experience (PRAGUE-16 study) - Widimsky, Petr; Koznar, Boris; Peisker, Tomas; Vasko, Peter; Vavrova, Jana; Stetkarova, Ivana (EuroIntervention, 2014)
AIMS: To assess the feasibility of direct catheter-based thrombectomy (d-CBT) performed jointly by cardiologists, neurologists and radiologists. METHODS AND RESULTS: Computed tomography (CT) was completed within <6 hours from onset of acute ischaemic stroke and excluded bleeding or developed ischaemia in 23 patients who fulfilled pre-specified entry criteria. The mean NIHSS was 17 (8-24). Mechanical recanalisation was successful in 19/23 patients (83%). The mean symptom onset – CT time was 81 min, CT – sheath insertion 47 min, sheath – reperfusion 46 min. Three patients died within 30 days, two others within 90 days (overall three-month mortality 22%). The mean mRs at 90 days for the entire group was 3.19, among survivors 2.31 and among survivors treated within <120 minutes 1.17. Favourable functional outcome (mRs ≤2) was achieved in 48% of patients. Five patients (22%) had full (mRs=0) or nearly full (mRs=1) neurologic recovery. Seven patients were able to be discharged from neurology ICU directly home after a short (<7 days) hospital stay. Two patients had symptomatic intracranial haemorrhage. CONCLUSIONS: Acute stroke treatment by d-CBT jointly by neurologists, cardiologists and radiologists provided promising results especially in patients reaching the cathlab within <2 hours from stroke onset.
Keywords: stenty; počítačová rentgenová tomografie; ischemie mozku; Brain Ischemia; Anesthesia, General; Humans; lidé středního věku; kooperační chování; Stroke; celková anestezie; Catheters; Female; Aged; dospělí; katétry; senioři; lidé; Radiography, Interventional; pilotní projekty; Pilot Projects; Thrombectomy; cévní mozková příhoda; trombektomie; Adult; Stents; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; Aged, 80 and over; srdeční katetrizace; Cardiac Catheterization; senioři nad 80 let; intervenční radiografie; mužské pohlaví; Cooperative Behavior